Perancangan Aplikasi Communication Board Berbasis Android Tablet Sebagai Media Pembelajaran dan Komunikasi Bagi Anak Tuna Rungu - Dhoni Indras Setyawan; Herman Tolle; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Sign language is used in the daily lives of people with hearing and speech impaired. One of the difficulties is how the deaf can inform the sign language used and can be understood by people who can hear so deaf people can communicate, interact, socialize, make friends, and dialogue occurs in everyday social. Prototype Application "PankoTuli" designed to help reduce the difficulties faced by the deaf and mute. Prototype Application "PankoTuli" this provides a method of Learning and Communications Indonesian Sign Language for the deaf and speech impaired quickly and practical for using the means of Android-based applications on smartphone devices. Applications Functional testing has been done with each of the test cases have been tested and properly, with the result declared all valid. Usability testing results obtained from satisfactory for the analysis of the application "PankoTuli" to achieve an average score of 68,32%.